REGRESSION ANALYSIS AND SIMPLE LINEAR CORRELATION FORECAST RESERVATION FOR GOODS USING TURBO PASCAL - Syarifah Syarifah; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2002)
In economic and business development, problems of uncertainty is a problem that always faced by the business and economic such as in predicting the volume and sales results for future periods. The role of statistics in economics and business is so good because statistics help companies especially the leadership in making decisions. In a decision the leadership must connect it with other factors such as power factor competition. To overcome this can be done using a statistical method in forecasting the value mencar ordering of goods is by simple linear regression and correlation.